External debt of Indonesia: From debt-led growth to growth-led debt? - Dita Kusumasari (Department of Development Economics, Universitas Sriwijaya, 2020)
Indonesia has received external debt as an external source of finance to fill in the investment-saving gap in achieving economic growth to improve social welfare. Despite Indonesian economy is able to recover to some extent, based on Bank Indonesia (2018), Indonesia’s external debt at the end of Q2/2018 still amounted to USD 355,7 billion; consisting of government and central bank external debt of USD 179.7 billion, as well as private sector (including state-owned enterprises) external debt of USD 176.0 billion. Therefore, this study aims to examine the trend and impact of external debt on economic growth in the context of Indonesia’s economy. If external debt is found to lead to debt trap, or already in the condition of growth-led debt, its benefits for economic development should be reviewed properly and government policies regarding external debt need to be redesigned. This study is a qualitative research in the form of case study of External Debt and its critical impact in Indonesia. Through observation, data comparison and literature study, it is found that external debt of Indonesia has been dominated by US Dollar and Japanese Yen, which assumed to cause surge in debt repayment.